Habitat Ecology of Epiphytic & Terrestrial Orchids in Langchenphu, Jomotsangkha Wildlife Sanctuary, Bhutan - Kelzang Choden; Jambay; Arjun Nepal; Choden; Bhagat Suberi (Indonesian Journal of Social and Environmental Issues (IJSEI), 2021)
Orchids are the largest and diverse families of flowering plants. Orchids are found growing mostly in tropical climates affecting various communities socio-economically. Among many protected areas in Bhutan, Jomotshangkha Wildlife Sanctuary (JWS) is the least explored in terms of flora and fauna. The study was carried out to assess diversity, host tree preferences and to determine the growth zone of epiphytic orchids along the altitudinal gradient in Langchenphu gewog in JWS. Transect technique was used in which three trails transect were laid out with 10 sampling plots in each transect. Plots size of 20 m × 20 m along the altitudinal gradients were established maintaining an altitudinal interval of 100 meters between each sample plot. A total of 42 species of epiphytic orchids from 20 genera was recorded of23 host tree species under 15 families were recorded. A significant correlation between diversity of orchid and altitude was observed (r = .927, p < .05). Myrtaceae and Theaceae were the most preferred host tree families (14%) followed by Bignoniaceae (13%) and others respectively. The Study concludes that 57% of total species encountered prefers higher canopy & on a tree with rough bark, Pearson chi-square test (X2(1) = 4.7, p< .05) showed a significant difference between trunk, branches, and canopy. Many epiphytic orchids prefer dense canopy (n = 73, 47%) and living trees (99%). Future studies should be focused more on the flowering season for obtaining better information on orchid diversity in the study area.